As-Sair Ilallah ( Jalan Menuju Allah ) - Safria Andy (SHAHIH (Jurnal Ilmu Kewahyuan), 2018)
“By tracing the various forms of worship used in accordance with Al-Quran and Al-Hadith accompanied by the patience of a servant as a manipulation of the application of understanding of both sources of Islam in the form of deeds and can answer the desire of the Sufis to know God Almighty, in walking to God. Through Taqarrub, suluk in reaching rihlah, through various different maqomat and ahwal that is adapted to both Islamic sources is an effort to reach it in the way of Allah SWT, which is wusul ilallah. All that is done in sair ilallah is the attainment to the realization of the essence of ihsan.”